KESADARAN HUKUM PENGAWAS PEMULA DALAM PEMILIHAN UMUM TAHUN 2024 DI KABUPATEN PEKALONGAN - Riayanah; Luluardi, Yunas Derta (Bawaslu Provinsi Jawa Barat, 2024)
The author conducted research with the following problem statement: What is the level of Legal Awareness among Election Monitors in the 2024 General Elections in Pekalongan Regency, and what factors influence this Legal Awareness? The research is classified as Empirical Juridical research with qualitative data processing methods. Data sources were gathered through observation, interviews, and documentation. A novel finding emerged regarding first-time election monitors, who are also first-time voters, referred to as beginners in the 2024 General Election. Based on the research results, it can be concluded that the legal awareness among beginner election monitors in Pekalongan Regency remains relatively low. Beginner monitors have yet to meet the indicators of Legal Awareness, such as Knowledge of Law, Understanding of the content of legal regulations, Attitudes toward regulation enforcement, and the formation of legal behavioral patterns. Factors influencing the legal awareness of beginner monitors include the legal certainty of Law No. 7 of 2017, the integrity in law enforcement by Gakkumdu, the availability of facilities and infrastructure, empowerment of monitors, and the presence of a Law Enforcement Community.